Relationship Between Irrigation Thresholds and Potato Tuber Depth in Sandy Soil - Matteau, Jean-Pascal; Celicourt, Paul; Shahriarina, Elnaz; Letellier, Philipe; Gumiere, Thiago; Gumiere, Silvio J. (Frontiers in Soil Science, 2022)
Soil disturbance resulting from tuber crop harvesting is a major threat to soil health. The depth of soil intervention is a critical factor that further strengthens the effects of such disturbance and makes the harvest one of the most harmful cropping operations. In the case of potato, soil moisture is a determinant factor for root and stolon development, hence, a deeper soil intervention may be required at harvest. While potato ranks as the fourth most cultivated crop worldwide, the impact of soil moisture on potato tuber vertical and horizontal distribution has received very little attention. The objective of this paper was to evaluate the effects of four soil matric potential thresholds (SMPTs; -10, -20, -30, and -45 kPa) on the spatial (vertical and horizontal) distribution of potato tubers grown in plastic containers filled with sandy soil using an X-ray computed tomography scanner. The results of the experiments conducted in a greenhouse environment suggest that the horizontal distribution of the tubers did not differ significantly across the irrigation treatments. However, a linear relationship between SMPT, and therefore irrigation threshold, and potato tuber depth was observed. In addition, the deepest tuber position was observed under the -10 kPa irrigation treatment, while the tubers were closer to the soil surface under the -45 kPa treatment, which could lead to a greater preponderance of tuber diseases such as late blight or greening. Thus, potato irrigation events implementing a SMPT between -20 and -30 kPa could reduce the harvest depth, hence, decreasing the negative impacts of soil disturbance on soil structural stability and soil organic carbon degradation while mitigating the impacts of disease as well as reducing fuel costs, greenhouse gas emissions, soil loss and erosion.